Hubungan Pola Makan Dengan Obesitas Pada Anak Sekolah Dasar - Siti Hajar Sangadji; Solehudin Solehudin; Indri Sarwili (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Childhood obesity remains a significant public health concern worldwide. Unhealthy dietary patterns characterized by excessive consumption of high-calorie, high-fat, and high-sugar foods contribute substantially to the increasing prevalence of obesity among school-aged children. Poor dietary habits developed during childhood may lead to long-term health consequences, including metabolic disorders, cardiovascular diseases, and psychosocial problems. This study aimed to identify the characteristics of respondents, describe dietary patterns and obesity levels, and analyze the relationship between dietary patterns and obesity among elementary school children at SDN Lenteng Agung 03 in 2023. This study employed a quantitative analytic design with a cross-sectional approach. The study involved 34 obese elementary school children selected using a total sampling technique. Dietary pattern data were collected using a structured questionnaire, while obesity status was assessed through anthropometric measurements and Body Mass Index (BMI) calculations. Data were analyzed using descriptive statistics and the Chi-Square test with a significance level of α = 0.05. The findings revealed that most respondents were male (64.7%) with a mean age of 9.97 ± 1.14 years. The majority of respondents had good dietary patterns (67.6%), while 32.4% had poor dietary patterns. Regarding obesity levels, 76.5% were categorized as Obesity Grade I, 14.7% as Obesity Grade II, and 8.8% as Obesity Grade III. The Chi-Square test demonstrated a statistically significant relationship between dietary patterns and obesity levels among elementary school children (p-value = 0.001). There is a significant relationship between dietary patterns and obesity among elementary school children. Children with poor dietary patterns tend to experience more severe obesity levels than those with healthier dietary patterns. Improving healthy eating behaviors is essential in preventing and controlling childhood obesity.